2021
DOI: 10.3390/ijerph18126216
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Validation of Cross-Modal Generative Adversarial Network for Sensory Substitution

Abstract: Visual-auditory sensory substitution has demonstrated great potential to help visually impaired and blind groups to recognize objects and to perform basic navigational tasks. However, the high latency between visual information acquisition and auditory transduction may contribute to the lack of the successful adoption of such aid technologies in the blind community; thus far, substitution methods have remained only laboratory-scale research or pilot demonstrations. This high latency for data conversion leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…For example, the authors of [12] used machine learning to examine the behavioral success using auditory encoding of a visual-auditory SSD; they proposed two cross-modal perception models for late-blind and congenitally blind individuals because their exposures to visual stimulation are different. In [30], a cross-modal GANbased evaluation method was proposed to find the optimal auditory sensitivity to reduce the transmission latency in visual-auditory sensory substitution. However, these studies have simply demonstrated the possibility of applying deep learning methods to SSD.…”
Section: Deep Learning For Visual-auditory Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the authors of [12] used machine learning to examine the behavioral success using auditory encoding of a visual-auditory SSD; they proposed two cross-modal perception models for late-blind and congenitally blind individuals because their exposures to visual stimulation are different. In [30], a cross-modal GANbased evaluation method was proposed to find the optimal auditory sensitivity to reduce the transmission latency in visual-auditory sensory substitution. However, these studies have simply demonstrated the possibility of applying deep learning methods to SSD.…”
Section: Deep Learning For Visual-auditory Conversionmentioning
confidence: 99%
“…approach to evaluate the efficiency of the encoding scheme and qualify the visual perception of a visual-auditory SSD. Our approach is similar to that employed in [12], [30] in that it uses vOICe as the encoding method for visual-auditory sensory substitution and creates synthesized visual data from the encoded audio signals by using a cross-modal GAN. However, we extend these approaches to obtain a method that yields an optimized design of the visual-auditory SSD algorithm and objectively quantify the visual perception from the behavioral analysis.…”
Section: A Architecture For Optimization Of Visual-auditory Conversionmentioning
confidence: 99%
“…Various studies have shown that people who are visually impaired show higher levels of auditory ability due to their frequent use in this population. These abilities are pertinent to auditory skills such as echo processing, voice localizing, and distance estimation [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%